Dissipative Assembly of Macrocycles Comprising Multiple Transient Bonds. (3rd June 2020) - Hossain, Mohammad Mosharraf; Atkinson, Joshua L.; Hartley, C. Scott
Abstract: Dissipative assembly has great potential for the creation of new adaptive chemical systems. However, while molecular assembly at equilibrium is routinely used to prepare complex architectures from polyfunctional monomers, species formed out of equilibrium have, to this point, been structurally very simple. In most examples the fuel simply effects the formation of a single short‐lived covalent bond. Herein, we show that chemical fuels can assemble bifunctional components into macrocycles containing multiple transient bonds. Specifically, dicarboxylic acids give aqueous dianhydride macrocycles on treatment with a carbodiimide. The macrocycles are assembled efficiently as a consequence of both fuel‐dependent and fuel‐independent mechanisms; they undergo slower decomposition, building up as the fuel recycles the components, and are a favored product of the dynamic exchange of the anhydride bonds. These results create new possibilities for generating structurally sophisticated out‐of‐equilibrium species. Abstract : Out‐of‐equilibrium assembly : Diacid precursors assemble into unstable aqueous anhydride macrocycles on treatment with carbodiimide chemical fuels, even though initial anhydride generation is unselective for cyclization versus polymerization. The efficiency of assembly results from both fuel‐independent (anhydride exchange) and fuel‐dependent (selective hydrolysis) mechanisms.